Adding psychological factor in the model of electricity consumption in office building - Susanty, Meredita (2015)
Due to rising economic costs and environmental concerns, many organizations have an interest in implementing campaigns aimed at reducing energy consumption. Researches indicate that energy behaviour is key to energy conservation and suggest that comparative feedback on energy usage can generate savings in residential and organizational settings. In implementing comparative feedback in workplace, there are two different ways to disaggregate collective energy consumption and apportion it to building users; apportionment to individual level or group level. This research uses agent-based modelling and simulation to examine the impact of applying different approaches of energy data apportionment to change staff behaviour toward energy consumption reduction. A simulation model of energy consumption in workplace which focuses on light and computer energy usage is created as a base model by re-implementing and simplifying a simulation model from former research. Several psychological factors and decision making mechanism are then being added to extend the base model. In addition to that, several experiments were run in the extended model to observer the most effective strategy between those two. The model divides staffs into four energy awareness stereotype based on staff motivation level, which are Big User, General User, Energy Saver and Environmental Champion. Sensitivity analysis suggests that motivation is an important factor in changing user’s behaviour and the experiment results indicates greater potential for energy saving when energy usage is apportioned to group level. The result also shows that users who have high motivation such as Energy Saver and Environmental Champion has similar energy consumption level and are significantly different with users who have low (Big User) and medium motivation level (General User). This significant difference makes Big User and General User should become the target of energy reduction campaign while Energy Saver and Environmental Champion are still expected to maintain their level of consumption.